UHPLC-FT-ICR-MS combined with serum pharmacochemistry for bioactive compounds discovery of Zhi-Zi-Da-Huang-decoction against alcohol-induced hepatotoxicity in rats. Issue 110 (15th November 2016) - Han, Fei; Liu, Tianfeng; Yin, Ran; Zhang, Xiaoshu; Ma, Li; Xu, Rui; Wu, Yawen
Abstract : In this study, a comprehensive strategy based on UHPLC-FT-ICR-MS and serum pharmacochemistry was developed to reveal the bioactive constituents of Zhi-Zi-Da-Huang decoction against alcohol-induced hepatotoxicity in rats after oral administration. Abstract : In the present study, a comprehensive strategy based on UHPLC-FT-ICR-MS and serum pharmacochemistry was developed to reveal the bioactive constituents of Zhi-Zi-Da-Huang decoction (ZZDHD) against alcohol-induced hepatotoxicity in rats after oral administration. The chromatographic separation was achieved on a Shim-pack XR-ODS C18 column (75 mm × 3.0 mm, 2.2 μm) using a gradient elution program with the detection performed on a Bruker Solarix 7.0 T mass spectrometer equipped with an electrospray ionization source in both positive and negative modes. By comparing the UHPLC-FT-ICR-MS fingerprints of blank serum and drug-dosed serum, and investigating the hepatoprotective effect of drug-dosed serum on BRL-3A cells from injury and then determining the relationship between the chemical components and pharmacological activities, a total of 18 compounds in rat serum were finally found to be the most potential bioactive components in ZZDHD, including 9 iridoid glycosides, 5 monoterpenoids, and 4 flavanones. Moreover, the ability of the UHPLC-FT-ICR-MS method and the UHPLC-Q-TOF-MS method for the discovery of bioactive compounds of TCMs was discussed. It could be concluded that the developed method is suitable for identifying and characterizing the bioactive components of ZZDHD. Furthermore, more precise data were obtained for further studying the relationship between the bioactive constituents and pharmacological activities of ZZDHD.